(untitled) (Global Journal of Human-Social Science, 2026)
Based on limited biographical information this paper tried to formulate some hypotheses concerning Pascal’s fascination with vacuum and dread of void and emptiness. Anzeu’s paper on Pascal’s phobia and early traumas including the death of his mother at age three could be further studied based on Green’s notion of the negative and the Botella’s study of figurability.